122k views
0 votes
Perform the indicated operation ​

Perform the indicated operation ​-example-1

1 Answer

3 votes

Answer:

(g o h)(t) = -4t² - 16t + 3

General Formulas and Concepts:

Pre-Algebra

  • Equality Properties

Algebra I

  • Composition of functions

Explanation:

Step 1: Define

g(t) = -4t + 3

h(t) = -t² + 4t

(g o h)(t) = g(h(t))

Step 2: Find

  1. Substitute: (g o h)(t) = -4(t² + 4t) + 3
  2. Distribute -4: (g o h)(t) = -4t² - 16t + 3

And we have our final answer!

User Henny Lee
by
5.2k points